Estimation of fatigue crack growth under complex loading using an accumulative approach. (2nd November 2017) - Kraemer, K. M.; Mueller, F.; Kontermann, C.; Oechsner, M.
Abstract: A model procedure to obtain estimates for thermo-mechanical fatigue crack growth rates based on isothermal test results is presented. This 'O.C.F.-model' consists of a linear accumulation of temperature independent fatigue crack growth and two temperature dependent crack growth parts. Temperature dependent crack growth is constituted from creep crack and oxidation damage. For the oxidative damage part, the formation of a γ ′-free zone at the crack tip and sub-sequent softening is considered to be determining. The possibility to assess creep crack growth in alloys with very limited creep ductility using linear-elastic fracture mechanics assumptions is investigated and compared to visco-plastic approaches. The isothermal data presented in this paper allows for an estimation of crack growth under both isothermal and anisothermal conditions with and without dwell times. Furthermore it allows assessing the fractions of crack growth caused by the different sources.